Ephemeroptera and Plecoptera biodiversity in central Patagonia, Chubut province, Argentina - Pessacq, Pablo (2008)
Aquatic insects in Central Patagonia (Andean Region), Argentina, have received poor and fragmentary attention. In this paper we present the first preliminary inventory of Plecoptera and Ephemeroptera taxa for the area and include seasonal records of adult stages. We incorporate a set of environmental features for the sampling sites and biotopes as well as the main characteristics of the phytogeographical and biogeographical areas in which the species were found. Twelve species and eight genera of mayflies and eleven species and five genera of stoneflies are recorded for the first time in Chubut province. The stoneflies Neofulla Claassen, Alfonsoperla flinti McLellan & Zwick, Austronemura eudoxiae Froehlich, Chilenoperla semitincta Illies, Neonemura illiesi Zwick and Potamoperla testacea Vera, and the mayflies Andesiops ardua (Lugo-Ortiz & Mc Cafferty), Chaquihua Demoulin and Oniscigastridae are new records for Argentina. Americabaetis Kluge, CamelobaetidiusDemoulin and Traverella Edmunds are confirmed for first time in the Andean Region (Central Patagonia province) and four Plecoptera and two Ephemeroptera species constitute new records for the Patagonian steppe. We also include two new records for Ephemeroptera and Plecoptera for the Santa Cruz province. We reinforce the idea that Patagonian aquatic environments have a highly specialized and complex insect fauna which can be correlated with biogeographical aspects but also with a great environmental heterogeneity.